Edukasi Pencegahan Anemia Pada Remaja Putri Melalui Peningkatan Asupan Zat Besi dan Pola Hidup Sehat - Nuryana, Riska; Nagaring, Sulaiman Putra; Lahay, Sitty Fadhilla Fitrianty (Lembaga Pengembangan Kinerja Dosen, 2025)
Anemia is one of the most common nutritional problems in the world and is mainly caused by iron deficiency. In Indonesia, the prevalence of anemia among adolescents remains high, especially in adolescent girls who have greater iron requirements due to growth and menstruation. Low levels of knowledge, unbalanced dietary patterns, and poor adherence to iron supplementation are the main factors contributing to anemia in this group. Therefore, efforts to increase knowledge through health education activities are needed. This Community Service activity aimed to increase the knowledge of adolescent girls about anemia prevention through improving iron intake and adopting a healthy lifestyle. The activity was carried out in Bongohulawa, Limboto District, Gorontalo Regency, on November 3, 2025, involving 40 adolescent girls. The methods used included health education, interactive discussions, demonstrations, and distribution of educational media. Evaluation was conducted using a pre-test and post-test. The pre-test results showed that only 25% of participants had good knowledge, while 45% had moderate knowledge and 30% had poor knowledge. After the educational intervention, the percentage of participants with good knowledge increased to 75%, moderate knowledge decreased to 20%, and poor knowledge decreased to 5%. It can be concluded that this educational activity was effective in increasing adolescent girls’ knowledge of anemia prevention and the importance of iron intake and a healthy lifestyle as early preventive measures.